An unusual case of dyspepsia - Khalid, Abdul; Baqai, M. Tariq (International Journal of Pathology, 2018)
A fifty six years old man presented with post prandial upper abdominal discomfort that gradually worsened overthe last three months. There was history of anorexia and vomiting associated with early satiety and weight loss.On physical examination, the patient had normal physical examination except that he was pale. Patient’s uppergastrointestinal endoscopy showed poorly distensible stomach with diffuse nodular growth involving distal part ofbody of stomach. The biopsy showed poorly differentiated large cell lymphoma of stomach. Less than 15% gastricmalignancies account for lymphomas. The majority of these tumors are Non-Hodgkin’s lymphomas of B-cell origin.Patient received chemotherapy (CHOP + Rituximab). Follow up endoscopic biopsies and PET scan at six wasnormal with no residual tumor activity.